HUBUNGAN MOTIVASI DENGAN UPAYA PENCEGAHAN KOMPLIKASI PADA PASIEN DM DI RUANGAN POLIKLINIK PENYAKIT DALAM INTERNE RSUP DR. M. DJAMIL PADANG TAHUN 2017 - Clara Nadia - (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Diabetes militus is a lifelong disease that can not be cured and can increase the risk ofdeath. In Indonesia there was a penile increase of diabetics militus from 8.4 million in 2011 toabout 21.3 million in 2030. The purpose of this study was to determine the relationship ofmotivation with prevention efforts of DM complication in polyclinic RSUP. Dr. M. DjamilPadang in 2017.Design in this research is Analytical Descriptive with cross sectional study approach.The time of the research from February to August 2017. The sample of this study amounted to72 people DM patients who visited the Polyclinic by sampling simple random sampling. Datacollection tool is questionnaire, univariate analysis by using descriptive statistics includefrequency distribution and percentage, bivariate by using chi square test.The results obtained 65.3% of respondents less in making efforts to prevent DMcomplications and 40.3% have high motivation. The result of bivariate analysis shows thatthere is a significant correlation between motivation with prevention effort of DMcomplication (p value = 0,000).Based on this research is expected to health officer to increase motivation of patientabout DM related prevention of DM complication.